Marty [videorecording (DVD)] - Mann, Delbert, 1920-2007; Borgnine, Ernest, 1917-2012; Blair, Betsy, 1923-2009 (MGM Home Entertainment, 2001)
Marty is the story of a 34-year-old Bronx butcher who fears that he will never find love, but at a Saturday night dance he meets a lonely schoolteacher with similar fears.